Performance Indicators (PINDICS) for Elementary School Teachers – A Means for Self-appraisal - YADAV, PADMA (THE PRIMARY TEACHER, 2014)
Performance Indicators (PINDICS) are designed to assess the performance and progress of elementary school teachers. These indicators have been developed by National Council of Educational Research and Training (NCERT) on the request of Ministry of Human Resource and Development (MHRD) for implementation of Sarva Shiksha Abhiyan (SSA) and Right to Education (RTE) Act, 2009.Every teacher ought to be competent in teaching that means, having rich knowledge base, favourable attitude towards teaching and learning, and innumerous skills for learning and transaction. High-quality teacher performance is essential for ensuring quality school education.Teachers should make continuous efforts to improve their performance. This tool PINDICS is mainly developed for helping teachers understand their performance level. By using this they will also be aware of their roles and functions and the expectations from them as an effective teacher. Teachers should use PINDICS as a self -development tool and continuously make efforts to reach the higher level and try to upgrade their performance. It can also be used by the administrators/supervisors/Head of the Institutions to appraise their teacher’s performance and should not be used for harassing teachers in any way.